A method for the stake-out of the seats in the conference room - Ata, Ercenk; Hoşbaş, Ramazan Gürsel; Pirti, Atınç (Geodesy and Cartography, 2022)
Before the application, the coordinates of the circle shaped seat places that will be applied in indoor space can be obtained by the help of common points determined in numerical project model formed in a local coordinate system. Practically, the coordinates of the points in the digital project model can be also obtained numerically by using the coordinates of the common points. However, converting to numerals manually, the factors such as the support quality of the project, exhaustion of the operator, hand tremble and screen resolution influence the sensitivity of the conversion to numerals. Errors made during the conversion negatively affect the coordinates of the points. The most suitable method not to make errors is the calculation of coordinates of the points in the project model by geodetic method. In this project, the calculation of the coordinates of the seat midpoints placed on the curves in a closed area, benefited from the corner point coordinates of the seats in the indoor space obtained from geodetic measurement in a local coordinate system before the application and benefited from the data of the other points of the indoor space are explained. Furthermore, the ground application of the midpoints of the seats on each curve row is explained. The accuracy of the stake-out of seats in the conference room is obtained between 1 and 2 cm.